Challenges in architectural design to support wind energy harvesting in Malaysia / Roslinda Ghazali, Siti Rasidah Md Sakip and Ismail Samsuddin - Ghazali, Roslinda; Md Sakip, Siti Rasidah; Samsuddin, Ismail (2021)
The effect of global climatic change directly influences our built environment. With the depletion of current fossil fuel, there are several drives for sustainable solutions towards generating energy for future daily consumption. Apart from employing solar energy, wind energy is also considered as an environmentally friendly solution to produce electricity. Foremost, the current standard of living for better quality of life requires uninterrupted supply of daily basic resources such as food, water, and electricity. This paper discusses the expansion of knowledge in wind energy and its theoretical studies on building integrated wind turbines (BIWT). The conclusion outlines challenges in the architectural design process to evaluate criterias for low-rise residential buildings in a low wind speed region.